Análise de desempenho de comunicação via rede LoRa para medição de energia elétrica em área urbana - Reck, Flávio Garlet (2024)
Recently, implementations of advanced metering systems for electricity have been verified worldwide, enabling the generation of coverage models for long-range communication. Monitoring the distribution of electric power is crucial for utility companies. However, to ensure effective monitoring, it is necessary to guarantee the best possible coverage, resulting in increased data reliability and reduced operational costs for the utility. Additionally, the possibility to remotely perform disconnection and reconnection operations for consumer units in case of non-payment brings benefits to both the utility, by reducing non-payment, and the consumer, particularly in terms of the prompt restoration of power. In this context, this work presents a comparative analysis of coverage models for long-range communication, as well as the development of a device for remotely disconnecting and reconnecting electric power, proving to be a relevant and practically impactful contribution to the field of electric power. The obtained results are crucial for consideration, especially in future expansions of the communication network in the involved cities or in new implementations in cities with similar topography and characteristics.